FAMILY PLATYSTOMATIDAE - Wendt, Lisiane Dilli (Zootaxa, 2016)
Platystomatidae (Signal Flies) are one of the largest families of Tephritoidea, with about 1200 species and four subfamilies, worldwide distributed. However, Platystomatidae are not well represented in the New World, and in the Neotropical Region only four genera and 26 species, belonging to Platystomatinae, are recorded. The family is a group understudied in Colombia and only one species is recorded to the country.